Dynamics of Islamic Education in Indonesia - Maulida Rizqia; Ahmad Dimyati (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This study aims to analyze the dynamics of Islamic education in Indonesia. The focus of this research includes aspects of the early growth of Islamic education in Indonesia, Islamic education during the Dutch and Japanese periods, as well as Islamic education during independence. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Then the data were analyzed and checked for validity through data triangulation. The results of this research conclude that the dynamics of Islamic education in Indonesia are divided into 3 aspects, namely (1) the initial growth was marked by establishing Islamic educational institutions in mosques or langgar, Islamic boarding schools, meunasah, Rangkang, and Dayah; (2) Islamic education during the Dutch and Japanese periods was characterized by a discriminatory and dichotomous attitude so that the development of Islamic educational institutions was very limited and received extra supervision, even the salaries of religious teachers were also limited; (3) Islamic education during the independence period was marked by Islamic education being taught formally in educational institutions as well as improving the quality of Islamic boarding schools and madrasas in teaching Islam.